THE ROLE OF BIOMARKERS AS A TOOL FOR SCREENING INDIVIDUALS WITH ARTERIAL HYPERTENSION AND ITS CONSEQUENCES - Olha L. Starzhynska; Mykola Yu. Kizlov; Olena O. Sakovych; Maryna O. Matokhniuk; Tetiana V. Polishchuk; Dmytro A. Bahrii; Svitlana V. Franchuk; Vadym M. Zhebel (Клінічна та профілактична медицина)
Introduction. Arterial hypertension (AH) occupies one of the leading positions in the structure of cardiovascular mortality, tripling the risk of cardiovascular events. Therefore, simple and effective tools are necessary for mass screening diagnostics of hypertension-induced myocardial damage, its dysfunction, and heart failure (HF).